Citrus Canker Management: Seasonal Preparation and Hurricane Irma’s Influence - Evan Johnson (EDIS, 2019)
The citrus canker season is just over a month away, so it is time to plan your canker management program to avoid fruit drop or fresh market quality loss.  With the current state of HLB in Florida, it is easy to forget some of the other potentially crop destroying pests in the grove.  Especially when, unlike HLB, their impact is heavily dependent on the weather.  Citrus canker can cause almost complete crop loss if environmental conditions are favorable for disease spread early in the season as is expected with heavy rains in the long-range forecast for this spring.  This crop loss comes from fruit drop induced by canker lesions on young fruit.  With properly timed and management, the midsummer canker fruit drop can be greatly reduced protecting yields.  Continued throughout the season it can also protect fruit quality.  In groves that had a major infection event from Hurricane Irma, especially young groves, the effects of Irma still pose a citrus canker management challenge.  Stem lesions that developed during the strong windblown rain of Irma will continue to be a troublesome source of inoculum even through long spells of unfavorable weather for canker.  Any grove that had canker develop from Irma will need to consider a strong canker management plan.